2021
DOI: 10.1002/cbin.11556
|View full text |Cite
|
Sign up to set email alerts
|

Validation of common reference genes stability in exosomal mRNA‐isolated from liver and breast cancer cell lines

Abstract: Accurate relative gene expression analysis by reverse transcription‐quantitative polymerase chain reaction relies on the usage of suitable reference genes for data normalization. The RNA content of small extracellular vesicles including exosomes is growingly considered as cancer biomarkers. So, reliable relative quantification of exosomal messenger RNA (mRNA) is essential for cancer diagnosis and prognosis applications. However, suitable reference genes for accurate normalization of a target gene in exosomes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…A clear band of PCR products on 1% agarose gel electrophoresis ( Fig 1B ), as well as not seeing primer dimers in the related melt curves, proved the specificity of the designed primers. The efficiency and specificity of these primers except hypoxanthine phosphoribosyltransferase 1 ( HPRT1) , TATA-box binding protein ( TBP ), and actin beta ( ACTB) were also studied in exosomal RNA of hepatic and breast cancer cell lines by our team recently [ 14 ]. However, here we confirmed their efficiency and specificity in cellular RNA of three hepatic and three breast cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A clear band of PCR products on 1% agarose gel electrophoresis ( Fig 1B ), as well as not seeing primer dimers in the related melt curves, proved the specificity of the designed primers. The efficiency and specificity of these primers except hypoxanthine phosphoribosyltransferase 1 ( HPRT1) , TATA-box binding protein ( TBP ), and actin beta ( ACTB) were also studied in exosomal RNA of hepatic and breast cancer cell lines by our team recently [ 14 ]. However, here we confirmed their efficiency and specificity in cellular RNA of three hepatic and three breast cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported the expression and stability status of reference genes for exosomal content of the same hepatic cancer cell lines as this study and SKBR3 as breast cancer cell line [ 14 ]. Interestingly, the geNorm showed almost similar stability ranking for cellular and exosomal content, in which B2M and YWHAZ were ranked as two stable reference genes (M value < 1) in Huh7, HepG2, and PLC-PRF5 cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, since exosomes are presently and commonly used to identify biomarkers in cancer, the identification of a suitable reference gene for exosome detection is also required ( 47 ). Gorji-Bahri et al ( 48 ) validated reference genes in pooled cancer exosomes, and Dai et al ( 49 ) revealed that GAPDH, YWHAZ and UBC were the most stably expressed reference genes in exosomal RNA isolated from liver and breast cancer cell lines. However, reference genes in HCC tissues and blood were not evaluated by in vitro experiments and another software analysis to determine stable housekeeping genes.…”
Section: Discussionmentioning
confidence: 99%